Antibacterial Activity and 16S rRNA Gene Sequencing of Lactic Acid Bacteria from Homemade Fermented Milk in Medan, Indonesia - Edwin Waroka; Edy Fachrial; I Nyoman Ehrich Lister; Muhammad Aditya Kurnia (Universitas Nahdlatul Ulama Surabaya, 2023)
Research indicates that fermented products have nutritional and non-nutritional components that can improve health. Milk is commonly used for fermentation products because its rich nutrients support the growth of Lactic Acid Bacteria (LAB). This paper investigates antibacterial activity and 16S rRNA gene sequencing of LAB from homemade fermented milk in Medan City, Indonesia. This paper was an experimental study by In Vitro Models conducted in August-October 2019. This study used three different homemade fermented milk (SF2-4) and positive control of manufactured fermented milk (SF1). All isolated LABs underwent an antibacterial assay by the Disc diffusion method against two pathogens, including Escherichia coli (Gram-negative) and Staphylococcus aureus (Gram-positive). In addition, there was molecular identification based on 16S rRNA gene sequencing. The zone of inhibition from samples against Escherichia coli ranged from 5.600-12.23 mm. The most potent antibacterial activity was found in SF4 (12.23 mm) and the least in SF2 (5.60 mm). Some samples (SF1 and SF2) showed no antibacterial effect against Staphylococcus aureus bacteria. The antibacterial activity against Staphylococcus aureus bacteria was found only in SF2 and SF3, which were 6.60 mm and 7.14 mm, respectively. Based on the characteristics, enumeration, and antibacterial activity, the authors chose isolated LAB from SF4 for molecular identification based on 16S rRNA gene sequencing. SF4 isolates had a similar 16S rRNA molecule to Lactobacillus fermentum strain NBRC 15885 with a homology level of 99.78%. In conclusion, some homemade fermented milk in Medan City, Indonesia, are potential probiotics.